PAIN SYNDROME IN CHILDREN: DIAGNOSTICS AND TREATMENT (WITH COMMENTARY BY R.F. TEPAEV) - R. F. Tepaev; A. N. Obedin (Педиатрическая фармакология)
Pain is one of the most common symptoms associated with a wide range of diseases. Ability to assess correctly and terminate pain is one of the key skills of a pediatrician. The article presents the modern data on pain physiology, humoral theory of pain syndrome development and clinical manifestations of neuropathic and nociceptive pain. The article presents the main issues of diagnosis and measurement of pain as one of the fundamental principles of pain syndrome management. On March 1, 2012, the World Health Organization published the new guidelines on the treatment of persistent pain syndrome in children. The article also provides recommendations on transition from the three-step “anesthetizing ladder” to the two-step one, which consists in the use of nonnarcotic, narcotic, adjuvant analgesics and combinations thereof.